2019
DOI: 10.1093/mnras/stz2431
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evolution of HC3N in dense molecular clouds

Abstract: We investigated the chemical evolution of HC 3 N in six dense molecular clouds, using archival available data from the Herschel infrared Galactic Plane Survey (Hi-GAL) and the Millimeter Astronomy Legacy Team Survey at 90 GHz (MALT90). Radio sky surveys of the Multi-Array Galactic Plane Imaging Survey (MAGPIS) and the Sydney University Molonglo Sky Survey (SUMSS) indicate these dense molecular clouds are associated with ultracompact HII (UCHII) regions and/or classical HII regions. We find that in dense molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
3
7
0
Order By: Relevance
“…This trend is consistent with the proposed evolutionary trend of HC 3 N (e.g. Urquhart et al 2019;Yu et al 2019) under the assumption that our Maser-only, Maser-RRL, and RRL-only sources correspond to YSOs, UC Hii regions, and normal classical Hii regions, respectively. 4.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This trend is consistent with the proposed evolutionary trend of HC 3 N (e.g. Urquhart et al 2019;Yu et al 2019) under the assumption that our Maser-only, Maser-RRL, and RRL-only sources correspond to YSOs, UC Hii regions, and normal classical Hii regions, respectively. 4.…”
Section: Discussionsupporting
confidence: 90%
“…Urquhart et al (2019) carried out a 3mm molecular-line survey towards a large sample consisting of 570 high-mass starforming clumps and found a trend in the detection rate of HC 3 N (J = 10-9), namely an increase from quiescent, to protostellar, to YSO, and then a slight decrease in Hii region (including all Hii region stages). Yu et al (2019) subdivided Hii regions into ultra-compact (UC) Hii regions and normal classical Hii regions. By analysing the archival available data from the Hi-GAL and the Millimetre Astronomy Legacy Team Survey at 90 GHz (MALT90) 9 , these latter authors found that the abundance of HC 3 N could increase in UC Hii regions, while it decreases or reaches a plateau in normal classical Hii regions.…”
Section: Evolution Of Hc 3 Nmentioning
confidence: 99%
“…Urquhart et al ( 2019) carried out a 3 mm molecular-line survey towards a large sample consisting of 570 high-mass starforming clumps and found a trend in the detection rate of HC 3 N (J = 10-9), namely an increase from quiescent, to protostellar, to YSO, and then a slight decrease in HII region (including all HII region stages). Yu et al (2019) subdivided HII regions into ultra-compact (UC) HII regions and normal classical HII regions. By analysing the archival available data from the Hi-GAL and the Millimetre Astronomy Legacy Team Survey at 90 GHz (MALT90) 9 , these latter authors found that the abundance of HC 3 N could increase in UC HII regions, while it decreases or reaches a plateau in normal classical HII regions.…”
Section: Evolution Of Hc 3 Nmentioning
confidence: 99%
“…Cyanoacetylene (HC 3 N), which is the shortest cyanopolyyne molecule, normally exists in warm and active star-forming regions (e.g. Yu et al 2019;Feng et al 2021). The University of Manchester Institute of Science and Technology (UMIST) database for astrochemistry 2 suggests that HC 3 N has four main formation pathways, including the neutral-neutral reaction between C 2 H 2 and CN, the neutral-neutral reaction between C 2 H and HNC, the ion-molecule reaction between C 3 H + n (n = 3-5) and nitrogen atoms, and the ion-molecule reaction between C 2 H + 2 and HCN (McElroy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…of the chemical evolution of molecular clouds [5] or -through the DC 3 N isotopologue -as proxy of the deuteration level prior to the formation of dense gas in star-forming regions [6]. Moreover, cyanoacetylene emission has been used to unravel the seasonal changes and atmospheric dynamics of the largest Saturn's moon Titan [7] and is predicted to be detectable in Super-Earth atmospheres by upcoming James Webb Telescope observations [8].…”
Section: Introductionmentioning
confidence: 99%